MERARIQ TRADITION: NEGOTIATION COMMUNICATION OBTAINING A WALI NIKAH IN NORTH LOMBOK - Andi Tamrin; Ali Ridho; Afna Fitria Sari; Wahyu Ilaihi (Aqlam: Journal of Islam and Plurality, 2024)
Abstract: Merariq tradition is a sacred tradition to obtain a wali nikah in marriage for the people of Genggelang, North Lombok, West Nusa Tenggara, Indonesian. In the process, it contains complicated negotiation communication between the two families of the prospective bride and groom. This research uses negotiation communication theory and the method applied is qualitative with a phenomenological approach. Data were obtained from interviews, observations, documentation and books and journals of national and international repute.  The formulation of the problems in this study are (1) why the Genggelang community conducts negotiation communication in the Merariq tradition; (2) how negotiation communication is carried out by the two families of the prospective bride to get a wali nikah. The result of the research is that in the implementation of the merariq tradition, a negotiation communication model is applied between the two families of the prospective bride and groom with the type of principled negotiation. Thus, the bargaining position of the two families of the bride and groom emphasizes the basis of kinship and togetherness. The use of integrative and distributive strategies to produce an agreement. Submission of ajikrama and pisuka as a sign that the bride and groom are getting married. However, the impact of compulsive negotiation communication causes ongoing conflict between the two families, this is contrary to the values of Islamic preaching. Keywords: Merariq, Tradition, Negotiation, CommunicationAbstrak: Tradisi Merariq adalah tradisi sakral untuk mendapatkan wali nikah dalam pernikahan bagi masyarakat Genggelang, Lombok Utara, Nusa Tenggara Barat, Indonesia. Dalam prosesnya, terdapat komunikasi negosiasi yang rumit antara kedua keluarga calon mempelai. Penelitian ini menggunakan teori komunikasi negosiasi dan metode yang digunakan adalah kualitatif dengan pendekatan fenomenologi. Data diperoleh dari hasil wawancara, observasi, dokumentasi dan buku-buku serta jurnal bereputasi nasional dan internasional.  Rumusan masalah dalam penelitian ini adalah (1) mengapa masyarakat Genggelang melakukan komunikasi negosiasi dalam tradisi Merariq; (2) bagaimana komunikasi negosiasi yang dilakukan oleh kedua keluarga calon mempelai untuk mendapatkan wali nikah. Hasil dari penelitian ini adalah bahwa dalam pelaksanaan tradisi merariq diterapkan model komunikasi negosiasi antara kedua keluarga calon mempelai dengan jenis negosiasi berprinsip. Dengan demikian, posisi tawar kedua keluarga calon mempelai lebih mengedepankan asas kekeluargaan dan kebersamaan. Penggunaan strategi integratif dan distributif untuk menghasilkan kesepakatan. Penyerahan ajikrama dan pisuka sebagai tanda bahwa kedua mempelai akan menikah. Namun, dampak dari komunikasi negosiasi yang bersifat kompulsif menyebabkan konflik yang berkelanjutan antara kedua keluarga, hal ini bertentangan dengan nilai-nilai dakwah Islam.Kata Kunci : Merariq, Tradisi, Negosisasi, Komunikasi